Prevalence and Determinants of Diarrheal Diseases among Under-Five Children in Horo Guduru Wollega Zone, Oromia Region, Western Ethiopia: A Community-Based Cross-Sectional Study - Kefalew Alemayehu; Lemessa Oljira; Melake Demena; Abdi Birhanu; Dasselegn Workineh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Diarrheal diseases are the leading cause of preventable death, especially among under-five children in developing countries, including Ethiopia. Although efforts have been made to reduce the morbidity and mortality resulting from diarrheal diseases, there is scarce information on the progress of the interventions against the burdens. Therefore, this study aimed to assess the prevalence of diarrhea and its associated factors in under-five children in Horo Guduru Wollega Zone, Oromia Region, Western Ethiopia. Methods. A community-based cross-sectional study was conducted. Of 12,316 households, 620 households that had under-five children were selected by simple random sampling technique from randomly selected kebeles. Before data collection, a pretest of the structured questionnaires was done on nonselected kebeles. Binary logistic regression was used to assess the association of the diarrheal diseases with independent variables. Finally, the odds ratio along with a 95% confidence interval was used to report the significant association between the outcome variable and its associated factors. A P value of ≤0.05 was considered statistically significant Results. The prevalence of diarrhea among under-five children was 149 (24%) (95% CI: 20.8, 27.3). Diarrhea was significantly associated with poor knowledge of mothers/caretakers on diarrhea prevention methods (AOR: 2.05, 95% CI (1.14, 3.69), being in the age group of 6–11(AOR = 1.546 (1.68, 3.52), and 12–23 months (AOR = 1.485 (1.84, 2.63)), families with poor wealth index (AOR: 2.41, 95% CI (1.29, 4.51)), children who were not vaccinated against measles (AOR: 4.73, 95% CI (2.43, 9.20)), unsafe child feces disposal (AOR = 3.75; 95% CI (1.91, 7.39)), inappropriate liquid waste disposal (AOR = 3.73 (1.94, 7.42)), and having two or more siblings (AOR: 3.11, 95% CI (1.81, 5.35)). Conclusion and Remarks. The prevalence of diarrhea among under-five children was high. There was a statistically significant association between diarrhea and age of the child (6–11 and 12–23), poor knowledge of mothers/caretakers on diarrhea prevention methods, families with poor wealth index, being unvaccinated against measles, improper liquid waste disposal, unsafe child feces disposal, and having at least two siblings. The findings have a significant policy inference for childhood diarrheal disease prevention programs. Therefore, educating mothers/caregivers on diarrheal disease prevention methods, child spacing, regular hand washing practice after disposing child feces, safely disposing liquid waste, and vaccinating all eligible children against measles should be a priority area of intervention for diarrheal disease prevention. Moreover, since these associated factors are preventable, the government needs to strengthen the health extension workers program implementations to reduce childhood diarrhea.